2010
DOI: 10.1097/jto.0b013e3181c6eb20
|View full text |Cite
|
Sign up to set email alerts
|

Split-Course Palliative Radiotherapy for Advanced Non-small Cell Lung Cancer

Abstract: A majority of patients experienced symptomatic improvement. The built-in 2-week break allowed for selection of patients for high-dose palliative radiation and balanced treatment benefits with potential side effects. Cancer survival was not adversely affected by treatments in this population with mostly advanced disease. This regimen is a viable option for patients who cannot tolerate a protracted, uninterrupted course of treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…Only prospective studies can determine whether uncompensated treatment interruption compromises quality of life. It should also be noted that a variety of palliative split-course radiotherapy regimens with quite long OTT have been developed which result in good symptom relief and duration of palliation [23]. Jones et al have stated that it is debatable whether compensation should be applied in all patients [4], and the present data support this view, at least when one focuses on overall survival.…”
Section: Discussionsupporting
confidence: 59%
“…Only prospective studies can determine whether uncompensated treatment interruption compromises quality of life. It should also be noted that a variety of palliative split-course radiotherapy regimens with quite long OTT have been developed which result in good symptom relief and duration of palliation [23]. Jones et al have stated that it is debatable whether compensation should be applied in all patients [4], and the present data support this view, at least when one focuses on overall survival.…”
Section: Discussionsupporting
confidence: 59%
“…The utility of split-course RT in rectal cancer has not been reported, and thus it is unclear whether such an approach is associated with a negative impact on outcome in terms of local control or survival. There are several examples in other cancer types, associated with reduced toxicity while maintaining efficacy (Pradier et al , 2004; Metcalfe et al , 2010; Fukuda et al , 2012; Gogna et al , 2012). The high metabolic response rates of the primary rectal cancer reported here support that this strategy warrants further study, but it should also be noted that split-course radiation was reported to have a negative impact in head and neck (Daoud et al , 2007; Miszczyk et al , 2014), gynaecological (Pedersen et al , 1994), and anal cancers (John et al , 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Thirty-four patients (71%) underwent their primary RT at our institution, whereas 14 patients were treated at our institution only upon recurrence. Although split-course radiation for bulky disease 10,11 was occasionally used at our institution during this timeframe, such patients were not included in this analysis; only 1 patient in this series was retreated to the thorax within 4 months of original thoracic radiation.…”
Section: Methodsmentioning
confidence: 99%